Anggaran Pendapatan Belanja Daerah dalam Pandangan Ekonomi Islam - Muhibin, Ahmad (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
This study aims to analyze the conformity of the Regional Revenue and Expenditure Budget (APBD) with the principles of Islamic economics within the framework of its regulatory and implementation aspects. The development of regional autonomy policies in Indonesia, initially regulated by Law Number 22 of 1999, later revised through Law Number 32 of 2004, and further refined in Law Number 23 of 2014, has contributed to a more structured system of regional financial management. The planning and budgeting mechanisms of the APBD are governed by various regulations, including Law Number 25 of 2004 concerning the National Development Planning System and Law Number 17 of 2003 concerning State Finance, as well as supported by other technical regulations. This research employs a library research method by analyzing various sources such as books, academic journals, and statutory regulations. The findings indicate that, normatively, the APBD regulations are aligned with the principles of Islamic economics, particularly in terms of justice, social welfare, and the protection of vulnerable groups. However, at the implementation level, such conformity cannot be fully assured. Therefore, further empirical studies are required to evaluate the effectiveness of budget allocation and the accuracy of program targeting in each fiscal period.